Upaya peningkatan efisiensi energi di Pupuk Kujang - Maryono Maryono (Jurnal Rekayasa Proses, 2008)
ACES21 is an urea manufacturing process technology which is the latest process of Toyo Engineering Corp. (TEC) with some advantages compared with previous technologies. ACES21 is designed with low investment cost and low energy consumption. Compared with the previous process some improvements have been done such as urea reactor that in the previous process was installed at a height of 20-22 meters above the ground, on ACES21 urea reactor was installed at ground level so that it can reduce construction costs. The synthesis process conditions where the urea formation reaction occurs is operated at relatively lower pressure than before that eventually reduces energy consumption. In addition to the ease and reliability of the operation, the urea plant has several on-line monitoring equipment that has not been widely applied such as nitrogen/carbon ratio monitoring, leak detector monitoring, and analyzer monitoring (ACES21, On-line Monitoring, ground Level). With the operation of Kujang IB that already uses ACES21 process, the energy consumption which in the previous process (Kujang 1A) was originally 8.324 Gcal/tonne of urea is reduced to 5.623 Gcal/tonne of urea, resulting in a significant energy saving.